Review for Ukrainian pharmaceutical market of hepatotropic drugs and determining the volumes of their consumption during 2016-2018 years - L. V. Iakovlieva; T. O. Bahlai (The State Expert Center of the Ministry of Health of Ukraine, 2020)
Hepatobiliary system and biliary tract diseases are common both in the world and in Ukraine (280,000 patients). According to the ATC classification, hepatotropic drugs are divided into three subgroups: А05А, А05В и А05С. The aim of this study was to analyze the assortment of drugs for the pharmacotherapy of diseases of the liver and biliary tract and the volumes of their outpatient consumption during 2016‒2018 years in DDDs/1 000 inhabitants/day. Drugs used for toxic hepatitis and presented in the pharmaceutical market of Ukraine were analyzed. The volumes of their outpatient consumption according to the ATC/DDD methodology based on the «Pharmstandard» system of the «Morion» company were determined, which also made it possible to analyze the assortment of drugs, to determine their dosage forms and manufacturing countries, and to analyze packaging prices. ATC codes identified eight subgroups of drugs, and 158‒167 TNs represent them during 2016‒2018 years. The largest number of TNs were presented A05AA02 Ursodeoxycholic acid (27‒30 TNs, including 19‒21 of foreign origin), А05ВА03 Silymarin (21‒23 TNs, including 9‒11 of foreign origin) and А05ВА50 Different preparations (Essentiale and etc. 35, 37, 34 TNs, including 22, 23 и 20 of foreign origin). Among all drugs of hepatotropic action in Ukraine in the 2018 year, foreign drugs amounted 74 TNs (44,3%) and domestic - 93 TNs (55,7%). The drugs of this group are delivered to Ukraine from 17 countries, the largest part is delivered by Germany (32% of drugs), India (12%), Austria (9%), Italy (7%). According to dosage forms, this group of drugs in 2018 was represented by 17 forms, mainly for the oral route (12 forms), 4 forms - for intravenous injection, and one - rectal suppository. The most consumed were: Different preparations including combined 3.9 DID, Silymarin - 1.48‒1.95 DID, Different preparations (Essentiale ® N, Essentiale ® Forte N, Hofitol) - 1.84‒2.08 DID. The market of drugs used for diseases of the liver and biliary tract in Ukraine in the 2018 year was represented by eight subgroups of 167 TNs, 44.3% of which are foreign-made. Total preparations were presented in forms for the oral route (12 forms), 4 forms - for intravenous injection, and one - rectal suppository. Every year, the consumption of hepatotropic drugs increased slightly: from 8.12 DID to 9.23 DID.